Microestrutura e propriedades mecânicas da liga Al7SiMg contaminada com 2,8%Fe e processada por fusão seletiva a laser - Pereira, Leandro Henrique (Universidade Federal de São Carlos, 2022)
The solidification kinetics imposed by Selective Laser Melting (SLM) leads the microstructure of the manufactured metallic components to present intrinsic characteristics such as: microstructural and phase refinement, elements in solid solution and columnar grains. The columnar grains formation during solidification can lead to hot cracking, as occur in the majority aluminum alloys, except for hypoeutectic alloys Al-10Si-0.6Mg, and Al-7Si-0.7Mg (%wt), which are commercial alloys widely used in SLM processes. Iron contamination occurs on a large scale in aluminum alloys and causes the formation of undesirable intermetallic phases, restricting the processing of these alloys. Therefore, the aluminum alloy Al-7Si-0.7Mg (%wt) was used as feedstock in this study, which 2.8 %wt of Fe was added. It is widely known in the literature that Fe has low solubility limit in aluminum matrix, and its presence must be carefully controlled. Iron content higher than solubility limit in AlSi alloys contribute to the formation of AlSiFe intermetallics with platelet-like morphology, which are responsible for degradation of mechanical properties. The Al-7Si-0.7Mg-2.8Fe alloy was obtained by Conventional Casting (CC), and processed by gas atomization and SLM. This study showed that the SLM processes is able to mitigate the deleterious effects caused by Fe-rich intermetallics on the mechanical properties of the Al-7Si-0.7Mg-2.8Fe alloy. Providing microstructural refinement, and rounding of AlFeSi phases and silicon particles, and appreciable amount of Si and Mg in solid solution, the alloy processed by SLM achieved excellent mechanical properties compared to the conventional casting alloy, and equivalents compared to Al-7Si-0.7Mg alloys with commercial composition present in the literature without iron contamination. The study opens up the possibility of expanding the use of primary aluminum alloys that suffer iron contamination, representing a new high added-value recycling route.
Microstructure and mechanical properties of Al7SiMg alloy contaminated with 2.8%Fe and processed by selective laser melting
Keywords: Fusão seletiva a lazer; Intermetálicos AlFeSi; Propriedades mecânicas; AlSiMg; Selective laser melting; AlFeSi intermetallics; Mechanical properties; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA